2021
DOI: 10.1186/s12875-020-01297-5
|View full text |Cite
|
Sign up to set email alerts
|

Reaching everyone in general practice? Feasibility of an integrated domestic violence training and support intervention in primary care

Abstract: Background Primary care needs to respond effectively to patients experiencing or perpetrating domestic violence and abuse (DVA) and their children, but there is uncertainty about the value of integrated programmes. The aim of the study was to develop and test the feasibility of an integrated primary care system-level training and support intervention, called IRIS+ (Enhanced Identification and Referral to Improve Safety), for all patients affected by DVA. IRIS+ was an adaptation of the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The ndings from this research are in line with and supported by other studies regarding online and phone consultations, presentations by survivors of DA in healthcare settings, and provision of remote support [22,29]. A report by the Health Foundation highlighted that many healthcare services had to adapt as a result of the pandemic and move towards a remote mode of working and that, in general, services that managed to adapt well relied on quickness and responsiveness as enablers of change [30].…”
Section: Discussionsupporting
confidence: 82%
“…The ndings from this research are in line with and supported by other studies regarding online and phone consultations, presentations by survivors of DA in healthcare settings, and provision of remote support [22,29]. A report by the Health Foundation highlighted that many healthcare services had to adapt as a result of the pandemic and move towards a remote mode of working and that, in general, services that managed to adapt well relied on quickness and responsiveness as enablers of change [30].…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the gap in knowledge and the lack of mandatory DV training, there is no major difference between dentists and medical doctors. Studies have shown that there is also a lack of training for medical doctors and a lack of knowledge on how to deal with victims [ 36 ]. In addition, many physicians do not know how to interact with special victim groups or have often overlooked males [ 37 ] and/or children [ 38 ] as victims and do not know how to support them well.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of integrated intervention increased preparedness after training in managing the complexity of DV in clinical practice; however, it was insufficient to catalyse identification and specialist referral. The lack of guidance in the usage of information about DV also has been reported as a barrier in practice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%